2014
DOI: 10.1017/jfm.2014.393
|View full text |Cite
|
Sign up to set email alerts
|

Highly resolved pulsatile flows through prosthetic heart valves using the entropic lattice-Boltzmann method

Abstract: Prosthetic heart valves have been widely used to replace diseased or defective native heart valves. Flow through bileaflet mechanical heart valves (BMHVs) have previously demonstrated complex phenomena in the vicinity of the valve owing to the presence of two rigid leaflets. This study aims to accurately capture the complex flow dynamics for pulsatile flow through a 23 mm St Jude Medical (SJM) Regent TM BMHV. The lattice-Boltzmann method (LBM) is used to simulate pulsatile flow through the valve with the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 44 publications
(52 reference statements)
6
32
0
Order By: Relevance
“…The platelets that flow through the b-datum leakage jet experience higher instantaneous damage for a longer period of time. This higher damage after leakage is possibly made worse by the asymmetric leakage jets in the diastolic phase as observed in a previous study [33]. The con tinuous interaction of the b-datum jet with larger vortices on the ventricular side may explain the higher damage experienced by platelets in b-datum leakage flows.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…The platelets that flow through the b-datum leakage jet experience higher instantaneous damage for a longer period of time. This higher damage after leakage is possibly made worse by the asymmetric leakage jets in the diastolic phase as observed in a previous study [33]. The con tinuous interaction of the b-datum jet with larger vortices on the ventricular side may explain the higher damage experienced by platelets in b-datum leakage flows.…”
Section: Discussionmentioning
confidence: 49%
“…17(c)), explaining why these platelets experience 1.76 times more accumulated damage than platelets flowing through valve housing gaps. It has also been shown that the fluid shear stresses at the b-datum jet are consistently higher (80-130 dynes/cm2) than those at the valve housing gaps (10-20 dynes/cm2) throughout the mid-diastolic phase [33].…”
Section: P E R P E N D Ic U La R V Ie W P O In Ts O F P La Te Le T P mentioning
confidence: 97%
See 3 more Smart Citations